Legal Protection of Creditors in Spin-offs: Comparing Indonesian and Philippine Corporate Law - Cut Tiara Sekar Maharani (Yayasan Cahaya Generasi Positif, 2026)
Corporate restructuring through demerger mechanisms perpetually triggers dogmatic tension between managerial efficiency and the protection of creditor constitutional rights. This article comprehensively compares creditor protection architecture within the corporate law jurisdictions of Indonesia and the Philippines. Utilizing a normative legal method with comparative approaches, this research explicitly exposes systemic weaknesses of Indonesian law. The Indonesian corporate legal regime proves highly fragile, relying purely on administrative procedural positivism through draconian objection deadlines and an impossible Actio Pauliana instrument. Conversely, the Philippine Revised Corporation Code offers absolute protection grounded in equity supremacy via the majestic Trust Fund Doctrine. This ancient doctrine positions corporate capital as an absolute trust fund for creditors, which instantaneously invalidates fraudulent asset transfers. As a primary academic conclusion, this research recommends paradigmatic hybridization for Indonesian corporate governance. Lawmakers now urgently must adopt these substantive principles by implementing a reversed burden of proof to entirely prevent corporate cannibalization crimes.